Consideration of the Position and Effects of Sacred Places in Urban Morphology in the Context of the Kaaba and its Surroundings - Sema Kızılelma (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
This research aims to explain the effects of holy places on urban morphology, based on the meaning of holy places arising from the needs of different beliefs, through different examples in the world. The effects of holy places on urban morphology will be explained through examples of holy places worldwide.  Finally, the existence of the holy places in the city, whose positions and beliefs in the world are discussed, are supported by the necessary maps and drawings, and their differences and similarities are emphasized. In light of these data, the effects of the changes in the structure and urban space on the urban morphology from the first construction of the Kaaba in the city of Mecca in the Hejaz region of Saudi Arabia to the present are examined. From the literature on urban morphology, "factors shaping urban morphology" have been revealed. The change in the urban morphology of the Kaaba and its surroundings is discussed through these factors. The study is expected to contribute to the literature by considering the concepts of sacred space and morphology through a concrete sacred space.